Efeitos dos óleos essenciais de orégano e alecrim na tolerância a estresses homólogos e heterólogos e respostas fisiológicas em Salmonella Enteritidis - Lira, Myrella Cariry (2019)
Salmonella enterica subsp. Enterica serovar Enteritidis is one of the prevalent serovars in food outbreaks and its persistence in food processing envoronments is in part due the ability to form biofilms on surfaces. The use of essential oils (OE) of Origanum vulgare L. (OVEO) and Rosmarinus officinalis L. (rosemary) have been proposed in food preservation systems as well as for surface disinfection. However, few is known about the effects of these substances on the tolerance of S. Enteritidis to stresses imposed during food processing, or about their mechanism of action against sessile cells in preformed biofilms. The present stuydy was performed in two steps using the S. Enteritidis 86 (SE86) strain, which was the responsible for more than 95% of the outbreaks occurred in the southern region of Brazil in the last decade, as a test strain. Initially, the influence of the rpoS, dps and ompR genes on the tolerance of SE86 to homologous and heterologous stressing agents after exposure to OVEO, ROEO and their major constituents carvacrol (CAR) and 1,8-cineole (CIN), respectively, was evaluated, by modeling viable cell reduction over time. In this step, the values of the minimal inhibitory concentration of OVEO (1.25 μL/ mL), CAR (0.62 μL/ mL), ROEO ( 20 μL/ mL) and CIN (10 μL/ mL) against SE86 were double-dilution higher than those against the Δdps, ΔrpoS and ΔompR mutants. The exposure to the same concentration of OVEO, CAR, ROEO or CIN caused higher reductions (up to 2.5 log CFU/mL) in Δdps, ΔrpoS and ΔompR mutants than in SE86 in chiken broth. In assays with homologous stressing agents, ompR, dps and rpoS influenced the tolerance to OEs and constituents. After adaptation to OVEO, CAR, ROEO and CIN, osmo- and acid tolerance of SE86 were influenced by rpoS gene, while thermotolerance was influenced by ompR. Tolerance of SE86 to sodium hypochlorite (NaClO) after adaptation to OEs and constituents was influenced by rpoS and dps. Subsequently, the ability of SE86, Δdps, ΔrpoS and ΔompR to form biofilm was evaluated in polystyrene microplate assays and it was observed that while SE86 was classified as strong forming the mutants did not form biofilm. The efficacy of OVEO and ROEO in the reduction of sessile cells of SE86 varied with exposure time and concentration, but no differences were observed between young and mature biofilms. In the scanning microscopical analysis, after exposure to OVEO or ROEO, SE86 non-cultivable sessile cells presented irregular morphology with bubbles or spots on their surface. Both, OVEO and ROEO showed a multitarget action on membranes by compromising the cell permeability and polarizarion, as well as efflux activity in SE86 sessile cells. Results of this study showed the influence of rpoS, dps e ompR genes on tolerance and capability to form biofilm of SE86, as well as the effects of OVEO and ROEO on physiological functions of membranes in this bacterium.